Gifted Learners’ Upbringing at Comprehensive School: Conflicting Actions and Their Management - Čiuladienė, Gražina (Acta Paedagogica Vilnensia, 2012)
Based on a survey of National Agency for School Evaluation, the peculiarities of gifted learners’ upbringing are described. The type of the problems is determined by the conflict of needs. The article seeks 1) to bring out the features illustrating the conflicting interaction between gifted learners and their classmates as well as teachers; 2) to reveal the potential of the needs’conflict management at school. The investigation embrased 8395 pupils aged 11 to 19 years (5th–12th grades) from Lithuanian basic, secondary schools and gymnasia. Data based on the content analysis of the External School Evaluation Report were also used. According to data analysis, the interaction between gifted learners and their classmates sometimes becomes conflicting: about 26 procent of pupils claimed that there was sneering at good learners; 47 percent of respondents claimed that they were disturbed to learn during some lessons. These ag gressive treatments were more common for younger pupils and those from basic schools. It has also been established that sometimes there is a conflicting interaction between gifted pupils and teachers, because the teachers don’t pay special attention to gifted pupils. About 35 percent of pupils said the teachers differentiated exercises for pupils of different abilities and paid more attention to gifted pupils. There were only a few schools among those 85 investigated, which had a school policy for their gifted learners. At these schools, there is a complex system consisting of defining the giftedness, identifying the gifted learners and supporting them. An effective school policy as regards able learners can manage conflicts between gifted learners and their classmates and teachers.